A prospective study of diathermy versus scalpel skin incision in abdominal surgery - Gupta, Arun Kumar; Singh Dall, Tejinder; Bansal, Darpan (International Surgery Journal, 2019)
Background: Various methods of skin incision have been identified in the recent past. Traditional skin incisions were made with stainless steel scalpel but recently electrocautery instruments like harmonic scalpel are also in use. With rise of seropositive cases, we aimed to evaluate whether the electrocautery can replace scalpel in operation theater, to avoid unfortunate injury to surgeons with scalpel. So we compared the usefulness of diathermy skin incision vs. scalpel skin incision in general surgical patients. Methods: This prospective study designed to include 120 patients admitted in the Department of General Surgery, Sri Guru Ram Das Institute of Medical Sciences and Research, Vallah, Sri Amritsar and who were undergoing elective abdominal surgical procedures namely cholecystectomy, appendectomy and inguinal hernia repair etc. Patients were randomly allocated into 2 groups of 60 patients each. In Group A, incision were made with electrocautery on cut mode and power set to 60-70. In group B, skin incisions were made with scalpel. Results: No statistical difference was found between group A and group B with regard to time of administration of pain killer injection, seroma formation, discharge being noticed from wound in both groups. Moreover the results were statistically non-significant for vascularity, pigmentation and pliability of wound observed. Conclusions: We concluded that electrocautery can effectively and efficiently replace scalpel in operation theater.